(untitled) (Nepal Journal of Epidemiology, 2015)
By investing in health protection, the health of the nation can be safeguarded from future threats of uncontrolled infectious disease epidemics and disasters. DOI: http://dx.doi.org/10.3126/nje.v5i1.12373